THE EFFECT OF MICROWAVE RADIATION FROM MOBILE PHONE TO PROTEIN CONTENT OF BEEF - fitriani, umi; Juswono, Unggul P; Widodo, Chomsin S (Department of Physics - Faculty of Science, 2014)
Hand phone (HP) is becoming a primary need after food, clothing and shelter. Hand phone is an electronic device that is capable of emitting microwave radiation. Although the radiation emitted by hand phones are essentially small, but capable of long user interactions potentially cause health problems or even damage to the tissue and cells. This study was conducted to determine the effect of duration of exposure and the distance ofÂ sources of hand phone radiation to the protein content of beef. Beef samples irradiated with long exposure variation 50, 60, 70, 80 and 90 minutes, and the variation of the radiation source spacing 1.5, 5, 10, 15 and 20 cm to the object. Then the sample was measured a protein content of beef by using UV-Vis spectrophotometer. The results showed a decrease in the percentage of protein content of beef irradiated from normal state with increasing duration of exposure, and otherwise the percentage of protein content of beefÂ with increasing distance of the radiation source. This occurs because intensity of radiation received increase with increasing of radiation exposure Â and decreasing of distance of the radiation source. The effect of duration of exposure and the distance of the radiation source to the protein content of beef as evidenced with decreasing the percentage of protein content occurred at the long exposure time of 90 minutes and the distance of the radiation source from material is 1,5 cm.